New Zealand as a safe adventure destination – is it a reality? - Salla, Purvi (Auckland University of Technology, 2014)
Adventure tourism has grown rapidly over the years playing a vital role in the economic growth of New Zealand as well as attracting numerous travellers from across the globe to the country. However, the adventure tourism industry has recently been in the limelight due to a multiple number of accidents in the adventure activities, which in turn have affected the country’s image as a safe adventure destination. The human and health costs associated with adventure incidents have lead the media to focus on the legal accountability of commercial adventure companies. The overall aim of this research is to analyse the safety practices adopted by the operators and examine the safety management framework implemented in the adventure tourism industry in New Zealand. A content analysis of news articles, blogs, and social networking sites was complimented with an analysis of adventure operator’s websites for safety precaution information adopted and published. Furthermore, the Health and Safety in Employment (Adventure Activities) Regulations 2011 were examined. The results suggest that there are significant loopholes in the new regulations, that there is considerable scope for improvement in the information provided on operators’ websites, and there is an ongoing perception that there is a lack of safety precautions. These results are compounded with the fact that the number of reported incidents/accidents within the adventure tourism industry have not decreased during the research period.
Keywords: Adventure tourism; Risk; Safety; Regulation; New Zealand